6 Neurodevelopmental Outcomes of Extremely Preterm Infants with Late-Onset Bacterial Sepsis According to Type of Bacteria. (29th October 2021) - Roychoudhury, Smita; Lodha, Abhay; Synnes, Anne; Ting, Joseph; Augustine, Sajit; Afifi, Jehier; Bizgu, Victoria; Shah, Prakesh; Soraisham, Amuchou
Abstract: Primary Subject area: Neonatal-Perinatal Medicine Background: Late-onset sepsis (LOS) is associated with adverse neonatal outcome. There is limited data on the long-term neurodevelopmental (ND) outcomes of infants based on type of bacteria causing LOS. We hypothesize that the type of bacterial pathogen causing late-onset sepsis influences the developmental outcome in extremely preterm infants. Objectives: To compare the neurodevelopmental (ND) outcomes at 18-24 months corrected age (CA) of infants born < 29 weeks who had late-onset sepsis (LOS) caused by: (1) gram-positive bacteria; (2) gram-negative bacteria; (3) mixed (both gram-positive and gram-negative bacteria); and (4) those with no sepsis (that is, no sepsis or culture-negative sepsis). Design/Methods: In this retrospective multicentre cohort study, we studied infants born at <29 weeks' gestational age (GA) between January 2010 and December 2017 and evaluated for neurodevelopmental assessment at 18–24 months' CA at nine Canadian Neonatal Follow-up Network centers. Infants with early-onset sepsis, major congenital anomalies, those who received palliative care at birth, those who died before 2 days of age, those with non-bacterial infections, and those lost to follow up were excluded. Exposure is late-onset sepsis (LOS) which is defined as the presence of a pathogenic organism in the blood or cerebrospinal fluid culture obtained from a neonate suspected of having sepsis after 2 days of age. The primary outcome was a composite of death or ND impairment (NDI) defined as the presence of any one of the following: cerebral palsy, Bayley-III score of <85 on any one of the components (Cognitive, Language, Motor composite score), hearing loss, and visual impairment. Demographic factors and ND outcomes were compared among the four groups using univariate and multivariate analysis. Results: Of the 3640 infants included, 823 (22.6%) had late-onset sepsis (LOS). Of the 823 infants with LOS, 569 (69.1%) infants had gram-positive sepsis, 172 (20.9%) had gram-negative sepsis, and 82 (10%) had mixed sepsis. Maternal and neonatal characteristics and outcome are reported in Table 1. Outcome data after adjustment for gestational age (GA), sex, antenatal steroids, SNAP-II score, small for gestational age (SGA), maternal age, and caesarian delivery are presented in Table 2. Conclusion: Late-onset bacterial sepsis, especially gram-negative sepsis and mixed infections, were associated with increased risk of composite outcome of death or neurodevelopmental impairment (NDI), or NDI alone, at 18-24 months corrected age (CA) in infants <29 weeks' gestational age (GA).